Assessing Training Interests of Latin American and Caribbean Immigrant-serving HIV/AIDS, STD, and Hepatitis C Providers in New York State, United States - Jahron P Marriott, MS; José G Pérez-Ramos, PhD; Song Hoa Choi, MA; Gersandre Gonsalves-Domond; Beatrice Aladin, MPA; Monica Barbosu, MD, PhD; Cheryl Smith, MD; Timothy Dye, PhD (Global Health and Education Projects, Inc., 2020)
Healthcare providers may be ill-equipped to address the specific care needs of refugee/immigrant (RI) patient populations. We assessed continuing education (CE) training interests among HIV/AIDS, STD, and Hepatitis C (HASH) providers in New York State (NYS), United States, who serve RI patients from Latin America and the Caribbean (LAC). An online survey was completed by 156 HASH providers during a three-month period in Spring 2018. HASH providers serving LAC patients indicate interest in additional training to address the unique needs of the RI community. We noted a strong interest for more tailored learning opportunities in issues that impact refugee health. Key words: • Immigrant Health • Refugee • HIV/AIDS • Latin America • Caribbean • Training • Continuing education • Hepatitis • STD   Copyright © 2020 Marriott et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.affect economic and health promotion.